From austere oligarchy to happy anarchy. Considerations on postmodernity - Gutiérrez Mozo, María Elia (Universidad de Lima. Carrera de Arquitectura, 2019)
In its ancestral service provision to human habitation, current architecture competes with other types of virtual habitation, alien to the immediacy and tangibility of its own territory over thousands of years around the world. Against overwhelming odds, but committed to win, architects confront with the challenge of persuading internet users to find themselves and their environment again by recognizing themselves in their self and circumstance, which are inseparable from each other. Through a provisional diagnosis of the “misplaced” situation of the third-millennium architecture, this paper aims to share the hope of a new “encounter of the first kind” of human habitation. To this effect, it explores reference books defining postmodernity and connects them to the features that, still nowadays, characterize it.